PROGRAM KOMUNIKASI PEMASARAN UNTUK MENINGKATKAN REVENUE FOOD & BEVERAGE 11/12 ROOFTOP BAR SEMARANG SEBAGAI PROGRAM MANAGER - Rafi Oktafiandi Akbar; Djoko Setyabudi (Interaksi Online, 2026)
The food and beverage industry in Semarang faces tight competition, causingfluctuating revenue at 11/12 Rooftop Bar due to sub-optimal promotional strategies. Thisstudy aims to implement an Integrated Marketing Communication (IMC) program focusingon event marketing and sales promotion to increase revenue. By combining elements likesocial media marketing, public relations, and advertising, various programs such as KorokkeHalloween Night, Sunset Rooftop Yoga, and targeted discounts were executed. The resultsindicate that these integrated activities successfully increased visitor numbers and revenueduring the program period. The study concludes that an IMC strategy based on eventmarketing and sales promotion effectively improves business performance and increases F&Brevenue.